Tinkering toward utopia : - Tyack, David B. (Harvard University Press, 1995)
In Tinkering Toward Utopia: A Century Of Public School Reform, David Tyack and Larry Cuban explore some basic questions about the nature of educational reform. Why have Americans come to believe that public schooling has regressed? Have educational reforms occurred in cycles, and if so, why? Why has it been so difficult to change the basic institutional patterns of schooling? What actually happened when reformers tried to "reinvent" schooling? Tyack and Cuban argue that the "ahistorical" nature of most current reform proposals magnifies defects and understates the difficulty of changing the system. Policy talk has alternated between lamentation and overconfidence. Tinkering Toward Utopia suggests that reformers today need to focus on ways to help teachers improve instruction from the inside out instead of decreeing change by remote control, and that reformers must also keep in mind the democratic purposes that guide public education. Tinkering Toward Utopia documents the dynamic tension between Americans' faith in education as a panacea and the moderate pace of change in educational practice.